Urban food prices under lockdown: evidence from Myanmar's traditional food retail sector during COVID-19. Issue 47 (8th October 2022) - Goeb, Joseph; Maredia, Mywish; Win, Khin Zin; Masias, Ian; Lambrecht, Isabel; Boughton, Duncan; Minten, Bart
ABSTRACT: Many governments imposed stringent lockdowns during the COVID-19 pandemic. With consumer incomes already depressed, the potential impacts of these measures on urban food prices are of particular concern, especially for poor or vulnerable households. This paper examines changes in urban food prices during lockdown using detailed food price data from family-owned retail shops – an important urban food supplier – in Myanmar's two largest cities, Yangon and Mandalay. We find that the supply side of Myanmar's traditional food retail sector was largely resilient to the shocks and lockdowns over the first six months of the COVID-19 pandemic. Estimates from a fixed effects difference-in-differences model reveal that food prices were 3% higher in townships under lockdown compared to those not under lockdown. Price differences were largest for raw or lightly processed commodities sourced through wholesale markets, which comprise a larger share of urban consumer's diets. We find no evidence of price gouging as retailer margins were not significantly different under lockdown restrictions. Our results suggest that the traditional food retail sector is an asset for food security, particularly in times of crisis.